Correction of Psychological Defenses and Anxiety of Students Using VR Training Programs - Pobokin P.A; Ivchenkova J.Y; Kapustina V.U (Moscow State University of Psychology and Education, 2021)
This paper describes the correction of psychological defenses and anxiety of students through virtual training programs to optimize the educational process. The materials of an empirical study obtained on a sample of students of Smolensk universities are presented. The study involved respondents (N=63) aged 18 to 25 years (M=19.4, SD=0.25), of which 84% were male, 16% were female. The study was conducted in several stages. For the correction of mental characteristics were used, the test "Anxiety Research" was used (questionnaire of Ch.D. Spielberger-Yu.L. Khanina), the "Lifestyle Index" methodology, a virtual reality program to overcome nyctophobia. The reliability of the results obtained on changes in anxiety indicators and mechanisms of psychological protection of students was checked using the Fisher statistical criterion (F). The obtained results make it possible to say that the most sensitive to the effects of VR in the framework of the conversation were protective mechanisms: repression, regression, substitution, denial, which change the assessment of what is happening and the adequacy of behavioral and emotional reactions. Indicators for the "rationalization" mechanism in the control group and in the experimental group also underwent changes, but without significant results.